Design and modeling of a planar graphene structure as a terahertz cyclotron radiation source - Jordan Planillo (Nature Portfolio, 2021)
Abstract With incredibly high carrier mobility and saturation velocity, graphene would be an ideal candidate for a miniaturized solid-state cyclotron radiation source. A planar semicircular graphene arc geometry was investigated for emission in the 0.5–1.5 THz range. Analytical studies, confirmed by finite element simulations, show that the emitted THz frequencies are inversely proportional to the arc radius given a fixed charge-carrier velocity. The simulations show that the desired frequency spectrum can be obtained with design radii ranging from 50 to 150 nm. Interestingly, the radiated spectrum is independent of the frequency of the stimulation of the graphene nano-arcs. The simulations also indicate that the total output power correlates well with the Larmor formulation. The device is expected to emit 1 nW/cm2, which confirms the findings of existing research in this field. Such a design could yield a scalable and cost-effective THz source.